PENINGKATAN KEMAMPUAN APRESIASI SASTRA SISWA SMP MELALUI MODEL INVESTIGASI KELOMPOK - Krismelinda Krismelinda; Widya Andayani; Rita Hartati; Tiarnita M.S. Siregar; Imelda Malawaty Simorangkir (Universitas Bengkulu, 2022)
The purpose of this study was to apply an effective learning model in increasing the ability to appreciate literature while at the same time increasing the interest and ability of the students of SMP Negeri 14 Binjai towards literary works. The research conducted was Classroom Action Research (CAR) with the research subject of 25 grade IX students of SMP Negeri 14 Binjai in the 2020/2021 academic year. The object of this research is the ability of students to rewrite the contents of the story (rewrite), retell the story (retell), and conclude the moral message as well as relate it to student life (reflection). The learning process to appreciate literature is carried out in two cycles through four stages, namely: the action planning stage, the action implementation stage, the observation stage, and the analysis and reflection stage. Based on the results of the study, it can be concluded that the students' ability to appreciate literature increases, this is indicated by the increase in the results of the three tests (rewrite, retell, reflection) of students at the end of each cycle. The average value of students' appreciation of literature has increased in each cycle, namely: 1) in the initial survey as many as 7 students (28%) of the total students who achieved a complete score, with an overall average score of 62.76; 2) in the first cycle, 15 students (60%) achieved a complete score, with an average overall score of 66.88; 3) in the second cycle there was a drastic increase in student mastery, namely a total of 25 students (100%) achieving a complete score with an average value of 78.8.